Saudi Arabia’s Economic Competitiveness in the Middle East - T. V. Naumenko; K. V. Timakhov (Vestnik MGIMO-Universiteta)
Saudi Arabia is one of the key economic players in the Middle East with a number of competitive advantages. The article analyzes these advantages as well as disadvantages and identifies measures to improve the competitive potential of Saudi Arabia. Methodologically it employs the Porter’s «diamond model». Cultural, historical and socio-political trends in Saudi Arabia increase the complexity of reforming the economy and increasing its competitiveness. The current reforms are insufficient to improve the quality of human capital. Existing economic and political institutions need to be reformed. There is an obvious problem of low women’s employment. Despite the fact that Saudi Arabia occupies only the 4th place on the regional competitive index table, authors see ways to strengthen this indicator of the Kingdom’s economy. The most decisive factor in this regard as argued by the authors is the elimination of state institutional problems which are chiefly responsible for low competitiveness of the economy.